Seasonal variation of Microsporidia MB infection in Anopheles gambiae and Anopheles coluzzii in two different geographical localities in Benin - Genevieve Tchigossou; Michel Lontsi-Demano; Eric Tossou; Pierre-Marie Sovegnon; Romaric Akoton; Danahe Adanzounon; Camille Dossou; Massioudou Koto; Azarath Ogbon; Marie Gouété; Godfrey Nattoh; Rousseau Djouaka (Malaria Journal)
Abstract Background Microsporidia MB, a naturally occurring Anopheles symbiont was shown to strongly impair Plasmodium transmission without imposing deleterious fitness effects on larval development, fecundity, adult survival, and adult sex ratio, and for these reasons it is being proposed as a promising tool for malaria control. However, there is a limited knowledge about its ecology, transmission dynamics in the environments with varying abiotic conditions, and whether these could impact on the mode of host transmission. This study aimed to determine the presence and prevalence of Microsporidia MB in rice fields in Benin during both the dry and wet seasons. Methods Anopheles larvae and adults were collected from rice fields and houses around rice fields in two locations (Koussin-Lélé and Magoumi). The collections took place during both the dry and wet seasons. The larvae and adults were molecularly identified to species level using molecular techniques and they were also screened for the presence of Microsporidia MB using PCR following standard protocols. Moreover, breeding sites were also analysed. Results The species identification results revealed that Anopheles coluzzii was the main species in Koussin-Lélé, accounting for 100% of the 1718 samples, while Anopheles gambiae sensu stricto (s.s.) was predominant in Magoumi accounting for 98.17% of the 986 samples. In Koussin-Lélé, Microsporidia MB prevalence of 14% (n = 276) was observed, whereas in Magoumi, only two samples (0.3%) were tested positive out of 667 screened in the dry season. During the wet season, the prevalence of Microsporidia MB symbiont was low with rates of 0.7% (5) in Koussin-Lélé and 0.6% (8) in Magoumi. However, the prevalence was relatively moderate in adult field collected mosquitoes with 3.09% (n = 1554) followed by larvae samples with 2.93% (n = 682) and adults emerged from field-collected larvae with 2.67% (n = 1235). Analysis of breeding sites revealed high concentrations of nitrate, nitrite and copper in Magoumi during the dry season, which was associated with a low prevalence of Microsporidia MB symbiont in this area. In the wet season, high concentrations of lead and nitrate were recorded in Koussin-Lélé with high concentration of copper in Magoumi, and both localities showed low prevalence of Microsporidia MB infection. Conclusion This study revealed a high prevalence of Microsporidia MB symbiont in Benin during the dry season. Further investigations might be necessary, and modelling of the prevalence and characteristics of breeding sites could help predict the presence of this symbiont in other locations and countries.